PENINGKATAN KOMPETENSI PROFESIONAL DOSEN (STUDI KASUS PADA FAKULTAS TARBIYAH DAN KEGURUAN UNIVERSITAS ISLAM NEGERI ALAUDDIN MAKASSAR) - Ismail, Muh. Ilyas (Jurnal Biotek, 2017)
This study aims to determine; 1) Development of professional competence of lecturer at Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar; 2) Lecturer Motivation at Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar; 3) Improving professional competence Lecturer Commitment to Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar, to improve professional competence. This research use case study approach. This research data source is 1. human element and 2. non human element, research instrument is researcher own function as a key instrument. Qualitative research data is narrative and data analysis techniques applied through three lines: 1. Data reduction, 2. Presentation of data, and 3. drawing conclusions. The validity of data is done four testing criteria, namely 1. Credibility, 2. Dependability, 3. Transferability, and 4. Confirmability. The research findings are; 1. Motivation model of lecturers who can improve their professional competence, that is because of the encouragement from within the lecturers and from outside the lecturers themselves. The encouragement from within the lecturer is the clarity of the lecturer’s career in the structural position, as well as the functional position of the lecturer. While the encouragement from outside the lecturers who are very influential in terms of achievement and mastering professional competence is the Dean of the Faculty of Tarbiyah and UG Teachers Alauddin Makassar. 2) The commitment model of a lecturer who can improve their professional competence is the dedication and service of the foundation of commitment. Therefore, to create a commitment of a lecturer to be synergy and intact buildings then the Dean of Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar must empower all lecturers, by involving lecturers in important decision making through Faculty senate. 3) Increasing the competence of professional lecturers will be beneficial to improve their professionalism in improving the quality of education. Therefore, the Quality Assurance Institution (LPM) is also considered to be very instrumental in increasing the professional competence of a lecturer. A lecturer needs to be equipped with new knowledge and diligence so that the lecturer can produce quality output